NMR-Based Quality Control Approach for the Identification of False Positives and False Negatives in High Throughput Screening - Dalvit, Claudio; Caronni, Dannica; Mongelli, Nicola; Veronesi, Marina; Vulpetti, Anna (Current Drug Discovery Technologies, 2006)
The quality of the data generated in a high throughput screening (HTS) run is fundamental for selecting bona fide inhibitors and for ensuring the capture of the full richness of inhibitors present in a chemical library. For this purpose a quality control filter based on three one dimensional (1D) proton NMR experiments is proposed. The approach called SPAM (Solubility, Purity and Aggregation of the Molecule) Filter requires the acquisition of a 1D reference spectrum, a WaterLOGSY spectrum and/or a selective longitudinal relaxation filter spectrum for the identified hits dissolved in aqueous solution and in the presence of a water soluble reference molecule. This palette of experiments permits the rapid characterization of the identity, purity, solubility and aggregation state of the active compound. This knowledge is crucial for deriving accurate IC50 and KI values of the inhibitors, for identifying false negatives and for detecting promiscuous inhibitors. Only compounds that pass through the SPAM Filter can be considered as starting points for medicinal chemistry efforts directed toward lead optimization. Examples of this approach in the identification of false positives in a screening run against the enzyme thymidine phosphorylase (TP) and the rescue of a false negative in a screening run against the Ser/Thr kinase AKT1 are presented.
Keywords: enzyme inhibitors